2013
DOI: 10.1007/s00705-013-1681-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus and hepatitis C virus in patients with human immunodeficiency virus infection in central China

Abstract: Co-infection of hepatitis B virus (HBV) and/or hepatitis C virus (HCV) with human immunodeficiency virus (HIV) has an adverse effect on liver disease progression. This study investigated the prevalence of HBV and/or HCV co-infection in HIV-infected patients in Central China. A total of 978 HIV-infected patients from Hunan Province were enrolled. HBV serum markers, anti-hepatitis-C-virus antibody (anti-HCV), HBV DNA, and HBV genotypes were analyzed. The prevalence of hepatitis B surface antigen (HBsAg) and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 36 publications
3
36
1
Order By: Relevance
“…In this study, we found that the positive rate of HBsAg for HIV-infected patients in Shaanxi Province was 11.7%, which was higher than the general population in either China or Shaanxi Province. A number of domestic studies have shown that the positive rate of HBsAg in the HIV-infected patients was higher than that of the general population, and it ranged from 13.1% to 19.4% [30][31][32][33]. However, on the contrary, some studies have reported that in HIV-infected patients, the HBsAg positive rate was slightly lower than that of the national general population.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this study, we found that the positive rate of HBsAg for HIV-infected patients in Shaanxi Province was 11.7%, which was higher than the general population in either China or Shaanxi Province. A number of domestic studies have shown that the positive rate of HBsAg in the HIV-infected patients was higher than that of the general population, and it ranged from 13.1% to 19.4% [30][31][32][33]. However, on the contrary, some studies have reported that in HIV-infected patients, the HBsAg positive rate was slightly lower than that of the national general population.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the rate of anti-HCV was 11.1% among HIV-infected patients in Shaanxi Province, which was also higher than in the general Chinese population, and 14-fold higher than in Shaanxi Province. Other studies have found both lower [35] and higher [32] HCV prevalences in HIV-positive patients, ranging from 2.2% to 62.4%. Pelton et al [57] found that 2357 cases of HIV/AIDS patients in Xinjiang had an anti-HCV positive rate of 38.0%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HCV infection shares the same transmission routes with HIV infection, which had been already observed cluster of disease in studies [12,13]. Especially for the intravenous drug users (IDUs), the prevalence of co-infection of HIV and HCV are high [14], and the HIV epidemics have association with geographic factors [15].…”
Section: Introductionmentioning
confidence: 91%
“…A cross‐sectional study showed 9.5% HIV‐HBV and 8.3% HIV‐HCV co‐infection rates in China, with the highest HIV‐HBV prevalence (14.5%) in Southeastern China and the highest HIV‐HCV prevalence in the Central region (28.2%), indicating that HBV and HCV prevalence is high in HIV‐positive Chinese population and differs by geographic region [Xie et al, ]. In central China, the rates of HIV mono‐infection, HBV/HIV dual infection, HCV/HIV dual infection, and HBV/HCV/HIV triple infection were 30.4%, 7.2%, 50.2%, and 12.2%, respectively [Chen et al, ]. Among injecting drug users in China, the infection rates were 0.3–20.1% for HIV/HBV and 15–31.8% for HIV/HCV [Zhou et al, , ], while in blood donors, the prevalence of HIV‐HCV and HIV‐HBV co‐infection was 41.83–85% and 2.5–12.49% in China [Dong et al, ; Yan et al, ].…”
Section: Introductionmentioning
confidence: 99%